The Relationship Between Daily Dietary Intake of Fiber and Short Sleep Duration in the Presence of Di(2-Ethylhexyl) Phthalate: A Population-Based Study - Lin, Jilei; Cheng, Siying; Zhang, Jing; Yuan, Shuhua; Zhang, Lei; Wu, Jinhong; Chen, Jiande; Tang, Mingyu; Zhao, Liebin; Yin, Yong (Frontiers in Nutrition, 2022)
Objective This study aimed to evaluate the relationship between daily dietary intake of fiber (DDIF) and short sleep duration (SSD) in the presence of di(2-ethylhexyl) phthalate. Methods Data of 13,634 participants in this study were collected from the National Health and Nutrition Examination Survey (NHANES). The sum of urinary mono-2-ethyl-5-carboxypentyl phthalate, mono-(2-ethyl-5-hydroxyhexyl) phthalate, mono-(2-ethyl)-hexyl phthalate, and mono-(2-ethyl-5-oxohexyl) phthalate was used to evaluate the level of di(2-ethylhexyl) phthalate (DEHP) exposure. The ln-transformed urinary creatinine-corrected DEHP [ln(DEHP/UCr)] level was used in the statistical models. DDIF was divided into tertiles (<5.77 g/1,000 kcal, 5.77–9.04 g/1,000 kcal, and ≥9.04 g/1,000 kcal). Results The 13,634 participants included in this study were classified into two groups according to sleep duration. The dose response analysis showed that higher ln(DEHP/UCr) was related to a higher risk of SSD (<7 h and <6 h). Participants in the highest vs. the lowest quartile of DEHP were found to be at increased risk of SSD (<7 h, <6 h, and <5 h). The result of risk of SSD <7 h was OR 1.57, 95% CI, 1.40–1.76; Ptrend <0.001, of SSD <6 h was OR 1.38, 95% CI, 1.18–1.61; Ptrend <0.001, and of SSD <5 h was OR 1.45, 95% CI, 1.13–1.86; Ptrend <0.001. DEHP exposure was found to be associated with SSD <7 h in a sex-specific manner (Pinteraction = 0.033). A significant interaction between ln(DEHP/UCr) and DDIF(tertiles1 vs. tertiles2) (Pinteraction = 0.02) was detected for SSD <7 h. Conclusion Our results showed that there was a harmful association between DEHP exposure and SSD (<7 h, <6 h, and <5 h). The ameliorative effects of median level of DDIF on SSD <7 h in the presence of DEHP exposure were observed in this study.